Biases in the selection stage of bottom‐up strategy formulation - Reitzig, Markus; Sorenson, Olav (Strategic Management Journal, 2013)
We propose that the failure to adopt an idea or innovation can arise from an in‐group bias among employees within an organizational subunit that leads the subunit's members to undervalue systematically ideas associated with members of the organization outside their subunit. Such biases in internal selection processes can stymie organizational adaptation and therefore depress the performance of the firm. Analyzing data on innovation proposals inside a large, multinational consumer goods firm, we find that evaluators are biased in favor of ideas submitted by individuals that work in the same division and facility as they do, particularly when they belong to small or high‐status subunits . Copyright © 2013 John Wiley & Sons, Ltd